The Empowering Marine Tourism in Indonesia Through the Crucial Role of BUMDES: Memberdayakan Pariwisata Bahari di Indonesia Melalui Peran Penting BUMDES - Fanji Tio Hardika; Achmad Riyadh (Universitas Muhammadiyah Sidoarjo, 2024)
This study examines the role of Village-Owned Enterprises (BUMDES) in developing the Tlocor Marine Tourism Village in Indonesia. Through qualitative research, including interviews, observations, and document analysis, the research highlights BUMDES Mitra Abadi's impact across economic, social, environmental, cultural, and political dimensions. Key findings show that BUMDES has significantly improved local economic conditions, promoted community involvement, enhanced environmental awareness, and strengthened cultural activities. However, challenges such as limited private investment and insufficient government support persist. The study underscores the need for continued backing from both the government and private sector to ensure sustainable tourism development in Tlocor. Highlights: 1. Economic Impact: BUMDES boosts local economies through community-based tourism.2. Community Involvement: Promotes social cohesion via diverse age group participation.3. Environmental Awareness: Enhances waste management and conservation efforts. Keywords: BUMDES, Tlocor Marine Tourism, community development, sustainable tourism, Indonesia